Permanently Displaced? : Increasingly Disconnected? Labor Force Participation in U.S. States and Metropolitan Areas - Hilgenstock, Benjamin (IMF Working Papers; Working Paper ;, 2018)
The United States stands out among advanced economies with marked declines in labor force participation. National averages furthermore conceal considerable within-country heterogeneity. This paper explores regional differences to shed light on drivers of participation rates at the state and metropolitan area levels. It documents a broad-based decline, especially pronounced outside metropolitan areas. Using novel measures of local vulnerability to trade and technology it finds that metropolitan areas with higher exposures to routinization and offshoring experienced larger drops in participation in 2000-2016. Thus, areas with different occupational mixes can experience divergent labor market trajectories as a result of trade and technology.